Pengaruh Efisiensi Biaya Bahan Baku, Efisiensi Biaya Tenaga Kerja Langsung, Dan Efisiensi Biaya Overhead Pabrik Terhadap Rasio Profit Marjin Pada Pt Cipta Karya Utama Medan - Rebecca Evadine; Harlen Silalahi; Dumariani Silalahi; Berlin Barus (Journal of Economic, Bussines and Accounting (COSTING), 2023)
The purpose of this study was to determine and analyze the effect of raw material cost efficiency, direct labor costs, and factory overhead efficiency on the profit margin ratio at PT Cipta Karya Utama in 2017-2021. The sampling technique of this study used saturated sampling with multiple linear regression analysis methods. The results showed that simultaneously the efficiency of raw material costs, direct labor costs, and factory overhead efficiency had a positive and significant effect on the profit margin ratio. While partially direct labor costs and factory overhead efficiency have no effect on the profit margin ratio. The test results for R Square is 0.207 which means 20.7% of the variation in the profit margin variable which can be explained by the independent variables of raw material cost efficiency, direct labor cost efficiency and factory overhead efficiency. Keywords: Raw Material Cost Efficiency, Direct Labor Cost, Factory Overhead Efficiency, Profit Margin Ratio